Record of Pampas cat, Leopardus garleppi (Matschie, 1912) in Humedales de Eten, Lambayeque, Peru - Aznaran, Wilmar (2021)
The pampas cat, Leopardus garleppi (Matschie, 1912), is one of the five species of the genus Leopardus known in Peru and is the only species of the genus that is distributed in the coastal desert ecoregion of Peru. Herein, we present a new record of L. garleppi through photographs for this ecoregion and the first one in the Eten Wetlands (Lambayeque department, Peru).